2020
DOI: 10.1016/j.adro.2020.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia and Radiation Dose to Circulating Lymphocytes With Neoadjuvant Chemoradiation in Esophageal Squamous Cell Carcinoma

Abstract: Purpose We hypothesized that radiation-induced lymphopenia could be predicted by the effective dose to the circulating immune cells (EDIC) in advanced esophageal squamous cell carcinoma treated with trimodality therapy according to the Dutch ChemoRadiotherapy for Oesophageal cancer followed by Surgery Study (CROSS) trial regimen. To test this hypothesis, we examined the effect of EDIC on the degree of lymphocyte drop (lymphocyte nadir). Methods and Materials Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Emerging evidence showing radiation-induced lymphopenia (RIL) or PLC-related parameters are associated with poor survival outcomes in several solid tumors (9)(10)(11)(12)(13)(14). Cho et al reported RIL was a potential predictor for ipsilateral breast tumor recurrence in 216 patients with early breast cancer treated with breast-conserving therapy (BCT) (15).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence showing radiation-induced lymphopenia (RIL) or PLC-related parameters are associated with poor survival outcomes in several solid tumors (9)(10)(11)(12)(13)(14). Cho et al reported RIL was a potential predictor for ipsilateral breast tumor recurrence in 216 patients with early breast cancer treated with breast-conserving therapy (BCT) (15).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that lymphocytes are responsible for the secretion of cytokines, which limit the proliferation and metastasis of tumour cells and a worse response to anti-cancer treatment. Lymphopenia is a negative prognostic factor in many cancers, including pancreatic cancer, non-small cell lung cancer (NSCLC), glioblastoma, and head and neck cancer [ 53 , 54 ]. Currently, there are a lack of effective methods to prevent the development of OM or to treat it.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the radiation dose to circulating lymphocytes has been reported recently. The integral dose to large blood vessels, the heart, and lymphoid or non-lymphoid organs, including the lungs or liver, is associated with the reduction in the number of lymphocytes and the subsequent development of lymphopenia [24][25][26]. Furthermore, because lymphocytes are the effector of immune response against the tumor cells, lymphopenia is expected to be associated with poor outcomes, such as those reported in various types of malignancies [18,27,28].…”
Section: Cancer Research and Treatment (Crt) 14mentioning
confidence: 99%